Surviving the influenza; The use of traditional medicines to combat the Spanish flu in colonial Indonesia, 1918-1919 - Ravando, Ravando (UI Scholars Hub, 2022)
The Spanish flu pandemic of 1918-1919 was widely regarded as the deadliest in modern history, claiming more lives than World War I. Colonial Indonesia was not spared. Several scholars have estimated that around 1.5 to 4.37 million people in the colony perished, making the death rate one of the highest in Asia. In the midst of the chaos and confusion caused by the pandemic, many people in colonial Indonesia turned to traditional medicines, particularly the poorer members of society who were inexperienced in Western medicine. Herbal treatment was considered a viable option for those who frequently faced discrimination when visiting Dutch clinics or hospitals. This essay demonstrates how more than a century ago, various ethnic groups in colonial Indonesia relied on nature to develop their own “vaccine” and medication in the fight against the Spanish flu. In the context of the pandemic, Sin Po and other newspapers played an essential role in spreading information about herbal medicines as an alternative, more affordable remedy than modern Western medicine. These newspapers provided the inspiration to investigate traditional Indonesian therapies more thoroughly. An examination of this subject reveals that there is nothing new under the sun. The colonial government never had a grand design to combat or stop the spread of a pandemic. It made almost no efforts at prevention and the outcome of this lack of preparedness was clear. Unfortunately, even more than a hundred years later, when COVID-19 struck Indonesia, nothing had really changed.